Evaluation of the collection material of tomato varieties in dagestan in order to identify the most promising forms for tomato breeding - P. M. Akhmedova; N. M. Velizhanov (Овощи России, 2022)
Relevance. Tomato is one of the main vegetable crops and is grown everywhere in the open and protected ground in the North Caucasus region of Russia. Therefore, increasing the production of tomato fruits in the open ground is an important task for vegetable growers in the south of our country. There is too much dependence on imported seeds. To get rid of this, it is necessary to increase breeding activity, create domestic varieties and hybrids of tomatoes with high potential productivity, resistant to adverse environmental factors and adapted to local growing conditions.Methods. The research was carried out at the experimental site of the Federal Agrarian Scientific Center of the Republic of Dagestan, located in the Primorsky lowland, at an altitude of 17 m above sea level. Agrotechnics is generally accepted in the Republic of Dagestan for tomato culture.Results. The results of the research indicate that most of the studied varieties and hybrids belong to plants of the determinant type of early maturation with average stability, with large and medium fruits of flat-rounded and rounded shape, with medium and high yields and relative resistance to fungal diseases. According to the largest number of fruits on the first brush, four varieties differ: Topaz, Yana, Chelnok, Talisman (6.5-5.7). On the basis of the "number of fruits" on the second brush, almost all varieties are marked, which is of interest to breeding. On the basis of the "distance between the brushes" varieties Yana, Marti, Grant, Perst, Topaz – are characterized by a generative (shortened internodes) type of plant (12-16 cm). The source material also differs in the shape of the fruit – 8 samples have a rounded, 3 samples have an elongated oval, 5 samples have a flatrounded and 2 samples have a cuboid shape of the fruit. The color of the fruits in the technical phase of ripeness in the studied varieties and lines was with (8 samples) or without (12 samples) an intense green spot. In biological ripeness 12 varieties and lines have a red color of the fruit.